2023
DOI: 10.30867/action.v8i4.1190
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution analysis and risk factors for stunting in Kerinci Regency, Jambi Province Indonesia

Rd. Halim,
Muhammad Syukri,
Guspianto Guspianto
et al.

Abstract: There are variations in the prevalence of stunting cases at the village level in Kerinci Regency. There have been no studies on the spatial distribution and risk factors of stunting cases in Kerinci Regency. This study aimed to determine the risk factors and spatial distribution of stunting. This research was conducted in Kerinci Regency from March to November 2020 using a case-control design and a total sampling technique. The study participants consisted of 223 patients and 223 controls. Children who experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…The study's findings in 2019 indicated hotspot cases in the Northwest Region of Kerinci Regency, specifically in the Sub-districts of Kayu Aro Barat, Kayu Aro, and Siulak Mukai. These results align with previous research by Halim et al (2023), which also identified clusters of stunting cases in the same area using a spatial analysis method with the Poisson model (Halim et al, 2023). Spatial analysis of stunting cases in Kerinci Regency, Indonesia, is crucial for understanding the distribution patterns and identifying hotspots of stunting prevalence.…”
Section: Discussionsupporting
confidence: 88%
“…The study's findings in 2019 indicated hotspot cases in the Northwest Region of Kerinci Regency, specifically in the Sub-districts of Kayu Aro Barat, Kayu Aro, and Siulak Mukai. These results align with previous research by Halim et al (2023), which also identified clusters of stunting cases in the same area using a spatial analysis method with the Poisson model (Halim et al, 2023). Spatial analysis of stunting cases in Kerinci Regency, Indonesia, is crucial for understanding the distribution patterns and identifying hotspots of stunting prevalence.…”
Section: Discussionsupporting
confidence: 88%